Clinical Characteristics at Initial Presentation and Impact of Dual Therapy on the Outcome of Bacteremic Streptococcus pneumoniae Pneumonia in Adults - K Weiss; DE Low; L Cortes; A Beaupre; R Gauthier; P Gregoire; M Legare; F Neoveu; D Thibert; C Tremblay (Canadian Respiratory Journal)
BACKGROUND: Approximately 10% of patients hospitalized with community-acquired pneumonia (CAP) are bacteremic. Bacteremic Streptococcus pneumoniae pneumonia (BSPP) is the number one cause of mortality, representing up to 70% of all CAP deaths. In fact, all CAP guidelines have identified this issue as one of the most important issues when establishing their recommendations.